Corruption is the Bane of Development (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Corruption is a major obstacle to development, hindering economic growth, deepening poverty, and exacerbating social inequality. It diverts public resources meant for development projects, such as healthcare, education, and infrastructure, into private hands, leaving essential services underfunded and inadequately delivered. This misallocation of resources reduces the efficiency and effectiveness of public spending, which in turn limits a country's ability to achieve sustainable development.  It also discourages investment by creating uncertainty and increasing the cost of doing business, thereby stifling job creation and economic expansion. It erodes public trust in institutions, undermines the rule of law, and contributes to political instability, making it difficult for states to implement sound governance and reform policies. In societies where corruption is pervasive, opportunities for social mobility are restricted, as access to services and rights often depends on one’s ability to pay bribes or leverage connections.